The Oxidative Stability of Chia Seed Oil Enriched with Oregano (Origanum vulgare L.) and Yarrow (Achillea millefolium) Extracts - Fatemeh Kiani Aliabadi; Asiye Ahmadi Dastgerdi; Javad Tabatabaeian Nimavard (Journal of Food Quality)
Oxidative stability of chia seed oil enriched with oregano (Origanum vulgare L.) and yarrow (Achillea millefolium) extracts at different concentrations (600, 1200, and 1800 ppm) was evaluated under accelerated oxidation conditions for 5 days. The total phenolic compounds and antioxidant activity of oregano extract were higher than the yarrow extract. With decreasing concentrations of extracts and increasing time, the oxidative stability of chia seed oil decreased significantly (p<0.05). At the first day, the acid value of chia seed oil did not show a significant difference, and the highest acid value was related to the control sample at the end of the storage period. The oil containing 1200 and 1800 ppm of oregano extract had the lowest acid, peroxide, anisidine, and Totox values. In the rancimat, the highest oxidative stability index (OSI) was shown in the sample containing 1800 ppm oregano extract, followed by yarrow extract. Our findings showed the potential of oregano and yarrow extracts by improving the oxidative stability of chia seed oil, especially at 1200 and 1800 ppm. At similar concentrations, oregano extract was more successful than yarrow extract in reducing the oxidation rate.